IMPLEMENTATION OF A COMPLIANCE RISK MANAGEMENT SYSTEM IN THE REPUBLIC OF UZBEKISTAN - Elbaeva Muqaddas Rashidovna (Journal Park Publishing, 2026)
This article examines the implementation of a compliance risk management system in the Republic of Uzbekistan amid ongoing institutional and anti-corruption reforms. It explores the essence of compliance and its importance for ensuring the legality, transparency, and effectiveness of government agencies and economic entities. It analyzes the regulatory framework governing compliance control, as well as its practical application in the public and corporate sectors. Particular attention is paid to the challenges and limitations of implementing compliance systems, including the shortage of qualified personnel and the need for further legislative improvements. The article outlines prospects for the development of a compliance risk management system, taking into account international standards and best practices.
Keywords: Compliance, compliance risks, compliance control, anti-corruption policy, corporate governance, Republic of Uzbekistan.